The effect of surface texturing in the sliding surface on tribological characteristics of alloy steel under wet condition - Hiralal S. Patil (Gruppo Italiano Frattura, 2021)
Surface texturing plays a significant role on the tribological performance of contact surfaces. The tribological characteristics are mostly dependent upon the different pattern and methods of surface texturing. This research works investigates lubricated wear behaviour on circular dimples textured EN-31 alloy steel materials using DUCOM linear reciprocating tribometer. The surface dimples are fabricated by micro-EDM and micro-drilling CNC methods. Initially plane surfaces are tested under different lubricants ISO-68 and ISO-220 oil on a couple of EN31 plates with EN8 steel pin. At loading conditions the results clearly shows that the ISO 68 oil gives better performance than ISO-220 oil in terms of frictional force and COF. The operation during test under ISO-220 oil observed is very noisy and wear rate is also more. Then after experiments under different load conditions on textured surfaces were investigated using optimized ISO-68 oil. An experimental results on m-EDM provides superior frictional characteristics with respect to m-CNC. Surface texturing may act as wear debris trapper, lubricant reservoirs, hydrodynamic lift, and retarding the lubricant molecules flow in a particular path where potential exists. Here micro-dimples EDM surface textures can enhance mixed lubrication and in mixed lubrication the friction is least and this may leads to decrement of wear loss.